Dependence of (Photo)electrochemical Properties on Geometry Factors of Hydrothermally Synthesized Delafossite Copper Gallium Oxide CuGaO2 toward Oxygen Evolution Reaction. Issue 10 (1st January 2018) - Mohan, Swati; Mao, Yuanbing
Abstract : The recent surge of alternative clean energy with minimal environmental impact in a cost-effective way has attracted great interest in the exploration of new materials and/or structures as efficient electrodes for industry-level (photo)electrochemical water splitting. Delafossites with a general formula of ABO2 as a type of earth-abundant materials are expected to serve as ideal alternatives for water electrolysis. In this work, by fine-tuning the synthesis procedure of delafossite CuGaO2 via surfactant assisted hydrothermal route, we investigated the dependence of their (photo)electrochemical properties on geometry factors. More specifically, the synthesized CuGaO2 samples were characterized by powder XRD, SEM, EDX, XPS, FT-IR, UV-Vis, and BET surface area measurements. Moreover, their electrocatalytic and photoelectrocatalytic performance were tested and compared toward oxygen evolution reaction (OER). Based on cyclic voltammetry and electrochemical impedance spectroscopy, their onset potential, current density, Tafel slope, charge transfer resistance, and stability were investigated. It was found that the synthesized delafossite CuGaO2 nanoflakes with the smallest dimensions exhibited the best (photo)electrocatalytic performance and could serve as a potential candidate for cost-effective and active electrode material.